Políticas comunicacionais e a prática radiofônica na sociedade em midiatização: um estudo sobre os documentos de comunicação do Movimento Sem Terra (MST) e Rádio Terra Livre FM - Guindani, Joel Felipe (Universidade do Vale do Rio do Sinos, 2010)
This research aims to present and understand the tension triggered between the political documentary propositions of the “Movimento Sem Terra – MST” (Movement of the Landless) on communication and operation of the “Rádio Terra Livre FM” (Radio Free Earth, MF [Modulated Frequency – MF]), demonstrating, in that case, evidence of the society in media coverage. Under the methodological model of participatory research, it also offers reflections on how the MST is dealing with the challenges from the growing social media coverage, with a view to their political idealizations of communication and their appropriation by militants who engage in the practice of communication. From the triad: (a) MST’s documents of communication, (b) Radio Free Land, MF, (c) Group of communicators - we are interested in knowing the causes of this inconsistency, delay/ difference or perhaps incompatibility and lack of articulation between the political formulations of MST on communication and operation of the Radio Free Land, MF. Our for
Keywords: midiatização; movimento sem terra; rádio; campos sociais; media coverage/mediatization; mst; radio; social fields; Ciências Sociais Aplicadas